1974
DOI: 10.1007/bf01250220
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of cattle against bovine ephemeral fever with live attenuated virus followed by killed virus

Abstract: SummarySerial passage of bovine ephemeral fever virus in hamster lung cells, HmLu-1, deprived rapidly the virus of virulence for cattle with simultaneous loss of the ability to produce neutralizing antibody. The attenuated virus thus obtained, however, could prime cattle to produce neutralizing antibody rapidly to high titers following a subsequent inoculation of formalin-inactivated, ALP04 geladsorbed vaccine (K). Although one subcutaneous dose of live vaccine (L) prepared from the attenuated virus produces n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Ben-Gera et al, (2015) concluded that "the Neethling vaccine is significantly more effective than protection conferred by X10 RM65 in preventing LSD morbidity". Our results also agreed with Inaba et al (1974) who found "that consecutive vaccination with live attenuated virus followed by inactivated virus resulted in a stronger and more durable neutralizing antibody response than vaccination with live attenuated vaccine alone or with two doses of the inactivated vaccine". Inactivated LSD vaccine did not provide high serological results i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Ben-Gera et al, (2015) concluded that "the Neethling vaccine is significantly more effective than protection conferred by X10 RM65 in preventing LSD morbidity". Our results also agreed with Inaba et al (1974) who found "that consecutive vaccination with live attenuated virus followed by inactivated virus resulted in a stronger and more durable neutralizing antibody response than vaccination with live attenuated vaccine alone or with two doses of the inactivated vaccine". Inactivated LSD vaccine did not provide high serological results i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Bovine ephemeral fever has been threatening cattle populations in Taiwan and other Asian countries even though vaccination has been imposed for three decades in these countries (Inaba et al, 1974). In this study, the authors, using serological and virological findings, analyzed the possible factors contributing to BEF epizootics in Taiwan: immunity coverage, virus phylogeny, and virus variation.…”
Section: Discussionmentioning
confidence: 99%
“…Cattle infected with BEFV show clinical signs such as sudden onset of fever and lethargy, which become a serious management problem especially in large-scale farming. Vaccines have been developed and vaccination was applied as a successful strategy for disease prevention and control (5,23,(26)(27)(28)(29). BEFV glycoprotein (G) is an important protein to induce a protective immune response in cattle (28).…”
Section: Discussionmentioning
confidence: 99%